Design and simulation of Cs2SnI6 based perovskite solar cell - Md. Arif Uddin; Sohanur Rahman; Tanha Zaman (Next Materials, 2025)
This study presents a computational investigation of a lead-free, stable, non-toxic and completely inorganic double perovskite solar cell based on Cs₂SnI₆, aimed at enhancing device performance through systematic simulation. Our study focuses on a comparative screening of multiple transport layers combinations and systematically optimizes interfacial and physical parameters specific to Cs₂SnI₆ solar cells. To identify the best suitable electron transport layer (ETL) and hole transport layer (HTL) seven different ETLs (TiO2, WS2, IGZO, WO3, PCBM, ZnO, ZnSe) and six different HTLs (Cu2O, CuI, p-MoO3, MoS2, CuSCN, SrCu2O) have been tested. Based on simulated photovoltaic performance, WS2 and SrCu2O are selected as the best compatible ETL and HTL, respectively. The study further explores the influence of thickness, bandgap, defect density, interface defect density, donor and acceptor density and operating temperature on device behavior. The effect of various back contact metals was also assessed. Finally, an optimized n-i-p structured device, FTO/WS2/Cs2SnI6/SrCu2O/Ni achieved a notable open circuit voltage (Voc) of 1.06 V, short circuit current (Jsc) of 30.82 mA/cm2, fill factor (FF) of 87.11 % and a high-power conversion efficiency (PCE) of 28.43 %. This work contributes to the advancement of environmentally friendly perovskite solar cells and provides valuable design insights for high-performance Cs-based photovoltaic devices. The investigation was carried out by employing 1-Dimensional Solar Cell Capacitance (SCAPS-1D) software.